Bridget Jones [large type] : mad about the boy - Fielding, Helen, 1958- (Thorndike Press large print core series., 2014)
Londonite Bridget Jones faces the challenges of maintaining sex appeal as the years roll by, the nightmares of drunken texting, the skinny jean, the disastrous e-mail cc, total lack of Twitter followers, and TVs that need ninety buttons and three remotes to simply turn on.